Understanding the Impact of the Israel-Gaza War in 2023 on the Academic Performance and Well-being of Palestinian University Students: Perceived Loneliness and Academic Burnout - Qtoof, Khalid Ibrahim; Horoub, Ibrahim Mohammad (Dirasat: Human and Social Sciences, 2025)
Objectives: This study investigates the impact of the Israel-Gaza War on Palestinian university students in the West Bank, focusing on the relationship between perceived loneliness, academic burnout, and academic performance. Methods: The study is conducted through a correlational research design involving 400 students from four prominent universities in the West Bank, namely Palestine Polytechnic University (PPU), Hebron University (HU), Bethlehem University (BU), and Palestine Ahliya University (PAU). Results:. The study uncovers significant negative associations between perceived loneliness and academic performance as well as a positive correlation between perceived loneliness and academic burnout. Additionally, it identifies a negative correlation between academic burnout and academic performance. The findings emphasize the detrimental effects of loneliness and academic burnout on students’ educational attainment during the war. Conclusions: Based on the findings, the study emphasizes the need for targeted interventions to support students in conflict-affected regions. The study’s implications extend to other universities and policymakers, offering valuable insights for addressing the challenges faced by students amidst adversity.